Immunity and cancer: role of tumor-infiltrating lymphocytes in triple-negative breast cancer - Ana Tečić-Vuger; Robert Šeparović; Ljubica Vazdar; Mirjana Pavlović; Petra Linarić; Sanda Šitić; Martina Šepetavc; Damir Vrbanec (Libri Oncologici, 2021)
Tumor stimulates specific innate and acquired immune mechanisms. Main carriers of body’s immune response to tumor are T lymphocytes and main mechanism is killing of tumor cells by cytotoxic T lymphocytes CD8 +. In some cases, immune system can also have a protumor role, which is a paradox, given that it is known that the inflammatory state promotes tumor growth. One of the major characteristics of tumors is the evading of immune response, in particular by mechanisms of inhibition of active antitumor immune response via two major physiological inhibitory signals, CTLA-4 and PD1 / PDL1. Blockade of these checkpoints, that are T cell inhibitory mechanisms, has recently yielded best results in an immunotherapy approach to cancer treatment. Immune infiltrate in the tumor, as evidence of existence of an active intrinsic response of the organism, is heterogeneous, and composition often differs between different tumors and tumor cells, and mainly divides into two main cell lines: lymphoid and myeloid. On type of cell lines in the immune infiltrate and their activation and orientation depends the clinical response in different tumors. It is well known that immune infiltrate, especially tumorinfiltrating lymphocytes (TILs), can be predictive of response to therapy and have a prognostic role. In some solid tumors they are a good sign, while in some they signal worse prognosis. Numerous studies have evaluated role of lymphocytic infiltrate in breast cancer (BC) and, based on this knowledge, first consensus on standardization of TILs evaluation in solid tumors has been established on the BC model. Prognostic role of TILs in triple-negative breast cancer has received the most attention.